Clozapine-associated myocarditis and cardiomyopathy: Epidemiology, clinical picture, risk factors, and management - Baptista, Drs. Trino; Carrizo, Edgardo; Rojas, Nayibe; Fernández, Erika; Velez, Gabriela; Servigna, Mercedes; Serrano, Ana; Sandia, Ignacio (Gaceta Médica de Caracas, 2020)
Clozapine (CLZ) is the first-choice drug in the treatment of resistant schizophrenia but is also non-labeled used in dementia, bipolar disorder, severe anxiety, autism, and abnormal movement disorders, among many others. Clozapine’s use is limited by clinically-relevant side effects such as neutropenia, myocarditis, cardiomyopathy, gastrointestinal hypomotility, and pneumonia. Heart dysfunction, particularly myocarditis, while lower than 0.1-1 % per year, imposes a serious health risk. La clozapina (CLZ) es el fármaco de primera elección en el tratamiento de la esquizofrenia resistente, pero también se usa en la demencia, el trastorno bipolar, la ansiedad severa, el autismo y los trastornos anormales del movimiento, entre muchos otros. El uso de clozapina está limitado por sus efectos secundarios clínicamente relevantes, como neutropenia, miocarditis, cardiomiopatía, hipomotilidad gastrointestinal y neumonía. La disfunción cardíaca, particularmente la miocarditis, aunque es inferior al 0.1-1% por año, impone un grave riesgo para la salud.